Islamic Law In A Secular State : A Study Of The Distinctiveness Of Islamic Law In Indonesia - Maula, Bani Syarif (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2014)
As a country of the largest Muslim population in the world, Indonesia is not an Islamic state. However, Indonesian government still accommodates the aspiration of Muslims to practice their belief and even to implement some aspect of Islamic law (shari’a). Political situation in Indonesia and the aspiration of Muslim society have given the opportunity for shari’a to be implemented formally. Therefore, it is essential for the ruler in a new democratic environment to accommodate Muslim aspiration to implement shari’a law, especially in national levels.This essay concludes that mutual influences between local traditions and Islam has formed a distinct characteristic of social structure of Muslim society in Indonesia. The fact of this characteristic has made some Indonesian Muslim intellectuals realized that the classical “imported” shari’a was not suitable to Indonesian context. Therefore, contextualizing and reinterpreting Islamic law for Indonesian Muslims is actually the best effort to implement shari’a in Indonesia amongst many demands of re-installment of shari’a law.